Right main bronchus rupture associated with blunt chest trauma: a case report - Carime Díaz; Daniel F. Carvajal; Eliana I. Morales; Saveria Sangiovanni; Liliana Fernández-Trujillo (International Journal of Emergency Medicine, 2019)
Abstract Background Tracheobronchial injury is one of the least common injuries in the scenario of blunt chest trauma. However, around 81% of patients with airway injury die immediately or before arriving at the emergency department due to tension pneumothorax. It presents with non-specific signs and symptoms challenging prompt diagnosis. Case presentation A 15-year-old adolescent who was riding a bicycle suffered an accident when he fell down a cliff, approximately 5 m deep. Upon admission to the emergency department, he presented with signs of respiratory distress. The airway was secured and a thoracoabdominal angiography was performed. The image reported pneumomediastinum, a small right pneumothorax, areas of pulmonary contusion, and an image of loss of continuity in the anterior superior wall of the right main bronchus highly suggestive of bronchial rupture. The bronchial lesion was then confirmed by fiberoptic bronchoscopy. Taking into account the patient’s characteristics, conservative management was chosen, and the patient was transferred to the intensive care unit (ICU) where protective tracheal intubation was performed. Conclusions A delay in diagnosis increases the rate of complications, mainly infectious complications and the formation of granulation tissue that could potentially obstruct the airway, impacting the patient’s outcome. The first step in the management of these patients is securing the airway, which should be done immediately. The gold standard for the diagnosis and characterization of airway injuries is bronchoscopy as it is the most effective tool to assess topography, extent, and depth of the lesion.